Quality evaluation and pollen profile of honey samples from different locations - Ecem Bayram, Nesrin (Progress in Nutrition, 2019)
In this study, it is aimed to determine some physicochemical properties and pollen types of honey samples collected from different regions. Pollen profile, moisture content, HMF, proline, frutose/glucose and electrical conductivity were the parameters analysed in each honey sample. According to the results obtained in the present study, all honey samples from different geographic origins were found to be consistent, in terms of the parameters analyzed, with the values given in the Turkish Food Codex Honey Communiqué (2012).  It was found that only one honey sample did not comply with the values given in the Turkish Food Codex Honey Communiqué (2012) in terms of frutose/glucose ratio. As a result of the melissopalynological experiment, three honey samples were found to be unifloral (two Castanea sativa and one Astragalus spp.) and the others were found to be polyfloral honey. The results indicate that physicochemical properties of the honey samples produced at different locations in Turkey differ greatly in accordance with the diversity of the flora of the region.